Australian Aboriginal Otitis-Prone Children Produce High-Quality Serum IgG to Putative Nontypeable Haemophilus influenzae Vaccine Antigens at Lower Titres Compared to Non-Aboriginal Children - Clark, Sharon L.; Seppanen, Elke J.; Kirkham, Lea-Ann S.; Novotny, Laura A.; Bakaletz, Lauren O.; Cripps, Allan W.; Corscadden, Karli; Coates, Harvey; Vijayasekaran, Shyan; Richmond, Peter C.; Thornton, Ruth B. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Non-typeable Haemophilus influenzae (NTHi) is the most common bacterial otopathogen associated with otitis media (OM). NTHi persist in biofilms within the middle ears of children with chronic and recurrent OM. Australian Aboriginal children suffer exceptionally high rates of chronic and recurrent OM compared to non-Aboriginal children. NTHi protein vaccines comprised of antigens associated with both adhesion and persistence in a biofilm are under development and could be beneficial for children with chronic and recurrent OM. Understanding the ontogeny of natural antibody development to these antigens provides insight into the value of vaccinating with particular antigens. Methods: An in-house multiplex fluorescent bead immunoassay was used to measure serum IgG titres and avidity for three putative vaccine antigens: recombinant soluble PilA (rsPilA), ChimV4, and outer membrane protein 26 (OMP26) in sera from Australian Aboriginal otitis prone children (n=77), non-Aboriginal otitis prone children (n=70) and non-otitis prone children (n=36). Serum IgG titres were adjusted for age, and geometric mean concentrations (GMCs) were compared between groups using a univariate analysis model. Antibody avidity was calculated as a relative avidity index and compared between groups using ANOVA. Results: Australian Aboriginal otitis-prone children had lower serum IgG titers to rsPilA and ChimV4 than non-Aboriginal otitis-prone children (p<0.001), and non-otitis prone children (p<0.020). No differences were observed between serum IgG titres from non-Aboriginal otitis-prone children and non-otitis prone children. There were also no differences in the proportion of high avidity IgG specific for these antigens between these groups. Serum IgG titers to OMP26 were similar between all groups (p>0.670) although otitis-prone children had a higher proportion of high avidity antibodies to this antigen. Conclusions: Australian Aboriginal otitis-prone children had lower serum IgG titers to 2/3 major NTHi vaccine candidate antigens, suggesting these children are unable to develop persistent IgG response due to repeated NTHi exposure. These reduced IgG titres may relate to earlier and more frequent exposure to diverse NTHi strains in Aboriginal children through carriage or infection. These data suggest that Aboriginal children may benefit from immunisation with vaccines containing these antigens to increase titres of protective antibodies.